Northeast Asian Economic Cooperation and Economic Development of Inner Mongolia - Situation and Prospects - Enkhee, Jargalyn (Mongolian Journal of International Affairs, 2014)
No abstract available The Mongolian Journal of International Affairs; Number 6, 1999, Pages 64-73